Long-time strong-adhesion tissue repair patch and preparation method thereof

By adding specific components to the tissue repair patch to form a reinforced chemical bond, the existing patches have solved the problems of weak adhesion, insufficient mechanical properties and easy swelling, and long-term strong adhesion and efficient healing effects are achieved.

CN119499448APending Publication Date: 2025-02-25SHANDONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411394800.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing tissue repair patches have weak adhesion, short adhesion time, insufficient mechanical properties, and easy swelling, resulting in poor shedding and poor use.

Method used

The adhesive strength and swelling resistance are enhanced by adding specific adhesion components, anti-swelling components and photoinitiators to the patch matrix material to form chemical bonds of amide bonds, disulfide bonds and catechol groups.

Benefits of technology

It achieves long-term strong adhesion, improves the durability and comfort of the patch, reduces the risk of shedding, and enhances the protection and healing effect of oral ulcers and tissues in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499448A_ABST
    Figure CN119499448A_ABST
Patent Text Reader

Abstract

The invention discloses a long-time strong-adhesion tissue repair patch and a preparation method thereof, and the preparation method comprises the following steps: adding an adhesion component, an anti-swelling component and alpha-ketoglutaric acid into a colloidal aqueous solution of a patch matrix material to obtain a precursor solution; and pouring the precursor solution into a patch mold, carrying out ultraviolet curing, and drying the obtained gel to obtain the patch. From the selection of materials and chemical bonds, physical and chemical bonds such as amido bonds, disulfide bonds and catechol groups are combined, so that the adhesion strength is improved, the adhesion duration is prolonged, and the adhesive has excellent anti-swelling performance and mechanical performance, can effectively isolate external saliva, food residues and the like when being applied to the oral cavity, reduces infection of ulcer wounds, and has a good application prospect. The dental ulcer healing is accelerated, and the method also has a relatively good application prospect in the field of tissue repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of tissue repair patches, and specifically relates to a long-term strong adhesion tissue repair patch and a preparation method thereof, which can be used for long-term physical and chemical isolation of oral ulcers to protect wounds and accelerate healing. At the same time, the patch has a good adhesion effect on various organs in the body, such as bladder, tendons, stomach and other tissues, and has great application potential in tissue repair and other aspects. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Tissue repair refers to the process by which the body recovers damaged tissues through a series of physiological mechanisms after injury. This process is crucial to maintaining individual health, restoring function, and improving quality of life.

[0004] Among tissue damage occurring in the oral cavity, oral ulcers are a very common type, with a high incidence rate worldwide. Recurrent aphthous ulcers (RAU) are one of the most common types, with an incidence rate of 2% to 10% in the general population.

[0005] At present, oral ulcer patches, as a new treatment method, have many significant advantages, such as targeted drug release, sustained release effect, reduced drug waste, easy use and improved patient comfort. Due to the high incidence and recurrence of oral ulcers, the limitations of existing treatment methods and the need for local treatment, the development and use of ulcer patches are of great necessity. By providing a more effective, safer and more convenient treatment method, ulcer patches are expected to significantly improve the quality of life of patients, but the inventors have found that the current patches have the following problems:

[0006] (1) The patch has weak adhesion and short adhesion time in the oral cavity. Existing adhesive patch patents are mainly concentrated on traditional materials such as ethyl cellulose and polyvinyl pyrrolidone. These materials usually lack sufficient adhesion and stability. In addition, the complexity of the oral environment, daily activities such as eating, talking and swallowing will produce mechanical friction and pressure on the patch. These actions will cause the patch to be squeezed and displaced, making it more likely to fall off. Even due to the continuous renewal of oral mucosal cells, old cells fall off and new cells grow. This natural process will gradually weaken the adhesion between the patch and the mucosa, thereby accelerating the shedding of the patch.

[0007] (2) The mechanical properties of the patch are weak. The materials used in many patches, such as thin film polymers or gel materials, are insufficient in mechanical strength. These materials are easy to break or deform when chewing, talking, swallowing, etc. in the mouth. When the oral patch is broken or damaged, it cannot isolate food residues, saliva, and microorganisms in the oral environment, affecting the healing effect of the ulcer.

[0008] (3) The patch swells severely. The materials used in many patches are highly hydrophilic. These materials will swell significantly after contact with water. There is always saliva in the mouth, which will constantly contact and be absorbed by the patch, causing the patch material to swell. The swelling will reduce the contact area and adhesion between the patch and the oral mucosa, causing the patch to fall off easily. The volume of the swollen patch increases, which may cause discomfort to the patient and affect eating and speaking. In addition, the over-swollen patch becomes fragile and easily breaks or fragments under mechanical stress, further affecting the effect of use.

[0009] At the same time, tissues and organs such as the Achilles tendon, bladder, stomach, intestines, heart, lungs, esophagus, etc. may be broken or damaged due to external reasons or diseases, such as Achilles tendon rupture, bladder leakage, etc., resulting in tissue damage. The existing suture method for repairing tissue damage has the following problems:

[0010] (1) Traditional suture operations are complicated and require high professional skills. Different suturing methods are required for different scenarios, such as interrupted suture, continuous suture, lock-edge suture, and tension-reducing suture. Choosing the wrong suture method may lead to problems such as poor healing or scar hyperplasia.

[0011] (2) The recurrence rate of traditional suture suturing methods is high. For example, in traditional hernia repair, the hernia orifice is usually closed by suturing the hernia sac directly to the abdominal wall muscles or fascia. If too much tension is applied during the suturing process, this may cause continuous pressure on the tissue at the suture site, thereby increasing the risk of suture breakage and affecting wound healing. Summary of the invention

[0012] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a long-term strong adhesion tissue repair patch and a preparation method thereof. From the selection of materials and chemical bonds, amide bonds, disulfide bonds and chemical bonds such as catechol groups are combined to improve the adhesion strength and adhesion time, and have excellent anti-swelling properties and mechanical properties. If applied to the oral cavity, it can effectively isolate external saliva and food residues, reduce the infection of ulcer wounds, and accelerate the healing of oral ulcers. After being applied to tissues such as the Achilles tendon and bladder, it can also be used to repair tissue wounds in the body, replacing surgical sutures. It is simple to operate and has a good tension-reducing effect.

[0013] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0014] In a first aspect, the present invention provides a method for preparing a long-term strong adhesion tissue repair patch, comprising the following steps:

[0015] Adding an adhesive component, an anti-swelling component and α-ketoglutaric acid in proportion to a colloidal aqueous solution of a patch matrix material, and mixing them evenly to obtain a precursor solution;

[0016] The adhesive component comprises an adhesive component A, an adhesive component B and an adhesive component C, wherein the adhesive component A contains a carboxyl group, the adhesive component B contains a hydroxyl group, and the adhesive component C contains a thiol group;

[0017] The precursor solution is poured into a patch mold, UV-cured, and the obtained gel is dried to obtain a patch.

[0018] Adhesion component A contains carboxyl groups, which can form primary amine groups with amino groups on the tissue surface, and form hydrogen bonds with carboxyl groups on the tissue surface; adhesion component B contains hydroxyl groups, which can form hydrogen bonds with carboxyl groups on the tissue surface; adhesion component C contains sulfhydryl groups, which can combine with sulfhydryl groups on the tissue surface to form disulfide bonds, and has reducing properties, which can reduce the oxidation of hydroxyl groups.

[0019] The groups in the anti-swelling component lack polarity and are not easy to form limited hydrogen bonds with water molecules, making the hydrogel water-repellent and destroying the hydration layer, thereby enhancing the hydrophobicity of the hydrogel and further improving the anti-swelling ability of the patch.

[0020] α-Ketoglutaric acid is a photoinitiator that decomposes into active free radicals or cations under ultraviolet (UV) or visible light irradiation to initiate polymerization reactions.

[0021] In some embodiments, the patch matrix material is selected from one or more of hyaluronic acid, carboxymethyl cellulose, carrageenan, agar, poly(N-isopropylacrylamide), polyvinylpyrrolidone (PVP), poly(hydroxyethyl methacrylate) (PHEMA), poly(glycerol methacrylate) (PGMA), gelatin, or polyvinyl alcohol;

[0022] Preferably, the patch matrix material is gelatin.

[0023] In some embodiments, the adhesion component A is selected from at least one of acrylic acid, NHS-acrylic acid, or methacrylic acid.

[0024] Preferably, the adhesive component A is acrylic acid or NHS-acrylic acid.

[0025] In some embodiments, the adhesion component B is selected from at least one of tannic acid, caffeic acid, dopamine hydrochloride, gallic acid or pyrogallol.

[0026] Preferably, the adhesion component B is tannic acid.

[0027] In some embodiments, the adhesion component C includes but is not limited to α-lipoic acid, cysteine, glutathione (GSH) or taurine.

[0028] Preferably, the adhesion component C is α-lipoic acid.

[0029] In some embodiments, the anti-swelling component is selected from at least one of 2-phenoxyethyl acrylate, polydimethylsiloxane, n-hexane, hexadecanol, or cholesterol.

[0030] Preferably, the anti-swelling component is 2-phenoxyethyl acrylate.

[0031] The groups in the anti-swelling component lack polarity and are not easy to form limited hydrogen bonds with water molecules, making the hydrogel water-repellent and destroying the hydration layer, thereby enhancing the hydrophobicity of the hydrogel and further improving the anti-swelling ability of the patch.

[0032] In some embodiments, the mass ratio of the patch matrix material, water, the adhesive component, the anti-swelling component and α-ketoglutaric acid is (0.6-1.2): (1-2): (1-3.5): (0.15-0.3): (0.02);

[0033] In the adhesion component, the mass ratio of adhesion component A, adhesion component B and adhesion component C is (0.1-1):(0.1-1):(0.1-1).

[0034] In some embodiments, the mass ratio of patch matrix material, water, acrylic acid, NHS-acrylic acid, α-ketoglutaric acid, 2-phenoxyethyl acrylate, α-lipoic acid and tannic acid is 0.6-1.2:1-2:1-3.5:0.15-0.3:0.01-0.02:0.05-0.2:0.1-1:0.1-1.

[0035] In some embodiments, the precursor solution is ultrasonically defoamed and then poured into a patch mold.

[0036] In some embodiments, the power of the UV curing lamp is 10W-500W, and the UV curing time is 2min-12h.

[0037] Preferably, a 500W UV curing lamp is used and UV curing is performed for 2-10 minutes.

[0038] In some embodiments, the temperature for drying the gel obtained by UV curing is 25-45° C., and the drying time is 12-24 hours.

[0039] In some embodiments, the patch mold is one or more of polytetrafluoroethylene, PDMS, silicone, glass mold, etc.

[0040] Preferably, a glass mold is selected, and its thickness is 0.1-2 mm.

[0041] In a second aspect, the present invention provides a long-term strong adhesion tissue repair patch prepared by the preparation method.

[0042] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0043] (1) The present invention prepares a strong adhesion tissue repair patch by adding functional groups that can react with tissues, such as primary amino groups, catechol groups, and thiol groups, and then drying them after light curing. The strong adhesion tissue repair patch can firmly adhere to the tissue damage site and is not easy to fall off. It can also protect the tissue damage for a long time. When applied to the oral cavity, it can isolate the ulcer surface from irritants in the oral cavity, such as food and saliva, relieve pain and promote healing without affecting daily life and eating. It can be applied to tissue repair in the body, such as bladder leakage, Achilles tendon tear, etc., and can replace sutures to achieve a better tension reduction effect.

[0044] (2) The tissue repair patch of the present invention enhances the hydrophobicity of the hydrogel by introducing the anti-swelling functional group benzene ring, solves the swelling problem of traditional tissue patches, and improves the durability and comfort of the patch. The patch will not dissolve or deform quickly due to saliva immersion, and maintains long-term stability and effect. It has broad application prospects in improving the comfort of patients with oral ulcers. At the same time, it also has good adhesion to various tissues of the human body and can replace surgical sutures for tissue repair. It is simple to operate and has a good repair effect, thereby promoting tissue repair and healing.

[0045] (3) The long-term strong adhesion tissue repair patch of the present invention has good biocompatibility, low manufacturing cost, simple and easy-to-obtain materials, simple process steps, adjustable thickness, and strong adhesion, anti-swelling and mechanical properties, making the tissue repair patch an ideal choice for repairing tissues.

[0046] Advantages of additional aspects of the present invention will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0048] Figure 1 This is a schematic diagram of the preparation principle of a long-term strong adhesion tissue repair patch according to an embodiment of the present invention;

[0049] Figure 2This is a comparison chart of the lap shear strength of the tissue repair patches prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0050] Figure 3 This is an optical photograph of the long-term strong adhesion tissue repair patch prepared in Example 1 of the present invention;

[0051] Figure 4 The shear strength of the long-term strong adhesion tissue repair patch prepared in Example 1 of the present invention is compared with the oral patch currently available on the market;

[0052] Figure 5 This is a graph showing the variation trend of the lap shear strength of the long-term strong adhesion tissue repair patch prepared in Example 1 of the present invention over time;

[0053] Figure 6 This is the swelling rate curve of the long-term strong adhesion tissue repair patch prepared in Example 1 of the present invention after swelling for 7 days;

[0054] Figure 7 This is a comparison chart of the healing effects of the patch prepared in Example 1 of the present invention and the commercially available propolis oral ulcer membrane on oral ulcers in mice.

[0055] Figure 8 Optical photographs of the patch prepared in Example 1 of the present invention attached to a pig stomach, a pig tendon, a pig esophagus, and a pig bladder.

[0056] Fig. 9 The adhesion strength of the patch prepared in Example 1 of the present invention when attached to different tissues and organs. DETAILED DESCRIPTION

[0057] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0058] The preparation method of the long-term strong adhesion tissue repair patch is described in detail below with reference to specific embodiments.

[0059] Example 1

[0060] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0061] (1) Weigh 1.2 g of gelatin solid, add 2 g of water, heat to 65°C and stir until completely dissolved.

[0062] (2) 3.5 g of acrylic acid, 0.3 g of NHS-acrylic acid, 0.02 g of α-ketoglutaric acid, 0.05 g of 2-phenoxyethyl acrylate (PEA), 0.1 g of α-lipoic acid, and 0.2 g of tannic acid were added to the dissolved gelatin solution in sequence and stirred to obtain a precursor solution.

[0063] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 40° C. for 15 hours to obtain a long-term strong adhesion tissue repair patch.

[0064] Example 2

[0065] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0066] (1) Weigh 1.0 g of gelatin solid, add 1.5 g of water, heat to 60°C and stir until completely dissolved.

[0067] (2) 2 g of acrylic acid, 0.2 g of NHS-acrylic acid, 0.01 g of α-ketoglutaric acid, 0.1 g of 2-phenoxyethyl acrylate (PEA), 0.2 g of α-lipoic acid, and 0.2 g of tannic acid were added to the dissolved gelatin solution in sequence and stirred to obtain a precursor solution.

[0068] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 20 hours to obtain a long-term strong adhesion tissue repair patch.

[0069] Example 3

[0070] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0071] (1) Weigh 0.6 g of gelatin solid, add 2 g of water, heat to 60°C and stir until completely dissolved.

[0072] (2) 1.5 g acrylic acid, 0.3 g NHS-acrylic acid, 0.015 g α-ketoglutaric acid, 0.05 g 2-phenoxyethyl acrylate (PEA), 0.5 g α-lipoic acid, and 0.8 g tannic acid were added to the dissolved gelatin solution in sequence and stirred to obtain a precursor solution.

[0073] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 12 hours to obtain a long-lasting strong adhesion tissue repair patch.

[0074] Example 4

[0075] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0076] (1) Weigh 0.6 g of polyvinyl alcohol (PVA) solid, add 2 g of water, heat to 90°C and stir until completely dissolved.

[0077] (2) 1.5 g acrylic acid, 0.3 g NHS-acrylic acid, 0.015 g α-ketoglutaric acid, 0.05 g 2-phenoxyethyl acrylate (PEA), 0.5 g α-lipoic acid, and 0.8 g caffeic acid were added to the dissolved polyvinyl alcohol solution in sequence and stirred to obtain a precursor solution.

[0078] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 12 hours to obtain a long-lasting strong adhesion tissue repair patch.

[0079] Example 5

[0080] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0081] (1) Weigh 0.6 g of polyvinyl alcohol (PVA) solid, add 2 g of water, heat to 90°C and stir until completely dissolved.

[0082] (2) 1.5 g of methacrylic acid, 0.3 g of NHS-acrylic acid, 0.015 g of α-ketoglutaric acid, 0.05 g of 2-phenoxyethyl acrylate (PEA), 0.5 g of α-lipoic acid, and 0.8 g of caffeic acid were added to the dissolved polyvinyl alcohol solution in sequence and stirred evenly to obtain a precursor solution.

[0083] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 12 hours to obtain a long-lasting strong adhesion tissue repair patch.

[0084] Example 6

[0085] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0086] (1) Weigh 0.6 g of polyvinyl alcohol (PVA) solid, add 2 g of water, heat to 90°C and stir until completely dissolved.

[0087] (2) 1.5 g acrylic acid, 0.3 g NHS-acrylic acid, 0.015 g α-ketoglutaric acid, 0.05 g 2-phenoxyethyl acrylate (PEA), 0.5 g taurine, and 0.8 g caffeic acid were added to the dissolved polyvinyl alcohol solution in sequence and stirred evenly to obtain a precursor solution.

[0088] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 12 hours to obtain a long-lasting strong adhesion tissue repair patch.

[0089] Example 7

[0090] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0091] (1) Weigh 0.6 g of carboxymethyl cellulose solid, add 2 g of water, heat to 90°C and stir until completely dissolved.

[0092] (2) 1.5 g acrylic acid, 0.3 g NHS-acrylic acid, 0.015 g α-ketoglutaric acid, 0.05 g 2-phenoxyethyl acrylate (PEA), 0.5 g taurine, and 0.8 g caffeic acid were added to the dissolved polyvinyl alcohol solution in sequence and stirred evenly to obtain a precursor solution.

[0093] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 12 hours to obtain a long-lasting strong adhesion tissue repair patch.

[0094] Example 8

[0095] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0096] (1) Weigh 0.6 g of carboxymethyl cellulose solid, add 2 g of water, heat to 90°C and stir until completely dissolved.

[0097] (2) 1.5 g acrylic acid, 0.3 g NHS-acrylic acid, 0.015 g α-ketoglutaric acid, 0.05 g hexadecanol, 0.5 g taurine, and 0.8 g caffeic acid were added to the dissolved polyvinyl alcohol solution in sequence and stirred evenly to obtain a precursor solution.

[0098] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 45° C. for 12 hours to obtain a long-lasting strong adhesion tissue repair patch.

[0099] Comparative Example 1

[0100] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0101] (1) Weigh 1.2 g of gelatin solid, add 2 g of water, heat to 65°C and stir for 6 h until completely dissolved.

[0102] (2) 3.5 g of acrylic acid, 0.3 g of NHS-acrylic acid, 0.015 g of α-ketoglutaric acid, 0.05 g of 2-phenoxyethyl acrylate (PEA), and 0.2 g of tannic acid were added to the dissolved gelatin solution in sequence and stirred evenly to obtain a precursor solution.

[0103] (3) The glass vessel containing the precursor solution was placed under a 500 W ultraviolet lamp for photocuring for 2 minutes, and the resulting gel was dried at 40° C. for 15 hours to obtain a long-term strong adhesion tissue repair patch.

[0104] Comparative Example 2

[0105] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0106] (1) Weigh gelatin solid, add 2 g of water, heat to 65°C and stir until completely dissolved.

[0107] (2) 3.5 g of acrylic acid, 0.3 g of NHS-acrylic acid, 0.02 g of α-ketoglutaric acid, 0.05 g of 2-phenoxyethyl acrylate (PEA), and 0.1 g of α-lipoic acid were added to the dissolved gelatin solution in sequence and stirred to obtain a precursor solution.

[0108] (3) The glass vessel containing the precursor solution was placed under a 500W UV lamp for photocuring for 2 minutes, and the resulting gel was dried at 40°C for 15 hours to obtain a long-term strong adhesion tissue repair patch.

[0109] Comparative Example 3

[0110] A method for preparing a long-term strong adhesion tissue repair patch comprises the following steps:

[0111] (1) Weigh gelatin solid, add 2 g of water, heat to 65°C and stir until completely dissolved.

[0112] (2) 3.5 g of acrylic acid, 0.3 g of NHS-acrylic acid, 0.02 g of α-ketoglutaric acid, and 0.05 g of 2-phenoxyethyl acrylate (PEA) were added to the dissolved gelatin solution in sequence and stirred evenly to obtain a precursor solution.

[0113] (3) The glass vessel containing the precursor solution was placed under a 500W UV lamp for photocuring for 2 minutes, and the resulting gel was dried at 40°C for 15 hours to obtain a long-term strong adhesion tissue repair patch.

[0114] like Figure 2As shown, in Example 1, a patch containing both tannic acid (TA) and α-lipoic acid (LA) was prepared, in Comparative Example 1, a patch containing only tannic acid (TA) was prepared, in Comparative Example 2, a patch containing only α-lipoic acid (LA) was prepared, and in Comparative Example 3, a patch containing neither tannic acid (TA) nor α-lipoic acid (LA) was prepared. Pigskin pretreated by immersion in artificial saliva for 24 hours was used for lap shear test. It was found that the adhesion strength could be improved by adding tannic acid (TA) alone to provide catechol, and it was found that the adhesion strength could be improved by adding α-lipoic acid (LA) alone to provide sulfhydryl groups. However, the adhesion strength was the highest when both were added at the same time. The reason is that α-lipoic acid is a reducing agent in addition to providing sulfhydryl groups, which can reduce the oxidation of catechol groups to aldehyde groups to improve adhesion, and also reduce the oxidation of amino groups to improve adhesion. The synergistic effect of the two can maximize the adhesion strength.

[0115] The optical photograph of the patch prepared in Example 1 is as follows Figure 3 , as shown in a, and as Figure 3 As shown in b, it was firmly attached to the pig tongue that was pretreated in artificial saliva for 24 hours. The patch prepared in Example 1 was adhered to the pig skin that was pretreated in artificial saliva for 24 hours. After pressing with fingers for 30 seconds, it was peeled off at a speed of 10 mm / min on a universal tensile testing machine. Figure 3 , as shown in c, indicating that the prepared oral patch has high flexibility and adhesion to tissues such as the skin and tongue.

[0116] like Figure 4 As shown, a commercially available patch and the hydrogel patch prepared in Example 1 of the present invention were subjected to lap shear tests using pig skin soaked in artificial saliva for 24 hours. It was found that the strength of the prepared patch in the lap shear test was significantly higher than that of various commercially available oral patches, indicating that the hydrogel patch prepared in Example 1 has strong adhesion.

[0117] like Figure 5 As shown, several lap shear test samples of pig skin with the hydrogel patch prepared in Example 1 in the middle and the outer layer being immersed in artificial saliva for 24 hours were prepared. The pig skin was immersed in artificial saliva, taken out after 0h, 4h, 8h, 16h, 24h and 48h, and stretched at a speed of 10mm / min using a universal tensile testing machine. The test showed that the patch had a long adhesion time and still had strong adhesion strength after 48h in artificial saliva, indicating that the patch had good stability.

[0118] like Figure 6 As shown, the patches prepared in Example 1 were divided into 7 groups. The patches in the 7 groups were all immersed in artificial saliva. The patches were taken out at 1 day, 2 days, 3 days, 4 days, 5 days, 6 days, and 7 days, respectively. The surface moisture was wiped off and then weighed. The swelling rate was calculated by the ratio of the increased weight to the original weight. Figure 6This indicates that the patch has limited swelling, basically does not swell, has good stability, and can play a good role in isolating and protecting ulcers.

[0119] like Figure 7 As shown, the patch (Hydrogel) prepared in Example 1 was compared with the propolis oral ulcer membrane (Zizhu) (commercial) purchased from a pharmacy and ulcer mice without any treatment, and the observations were performed on 1 day, 3 days, and 5 days respectively. It was found that the oral ulcer healing effect of the mice in the patch group (Hydrogel) was the best and basically did not fall off, while the commercially available oral ulcer membrane basically fell off in 1 day and could not play a protective role, and the control group had basically no improvement, indicating that the patch prepared in Example 1 has a good protective and therapeutic effect on oral ulcer wounds.

[0120] like Figure 8 As shown in a, the patch prepared in Example 1 can be firmly attached to the pig bladder and can be continuously washed by water flow without falling off. Figure 8 As shown in b, the patch prepared in Example 1 is attached to the inner wall of the pig esophagus. Figure 8 As shown in c and d, the patch prepared in Example 1 is attached to the pig tendon. Figure 8 As shown in Figure e, the patch prepared in Example 1 is attached to the pig stomach, which shows that the patch prepared in Example 1 also has a good adhesion effect on tissues and organs, and has great application prospects in the repair of wounds in the body.

[0121] like Fig. 9 As shown, the patch prepared in Example 1 was subjected to lap shear tests on various tissues and organs, pig bladder, pig heart, pig stomach, pig tendon, pig intestine, and pig lung immersed in PBS buffer, and it was found that the patch had good adhesion to various tissues and organs, indicating that the patch has great application prospects in the fields of tissue repair and the like.

[0122] The long-term strong adhesion tissue repair patch provided in the above embodiment has a simple preparation process, strong adhesion and excellent anti-swelling performance. It is attached to the surface of oral ulcers to play a good role in protecting oral ulcers, isolating bacteria and solid saliva residues in the oral cavity, and accelerating the healing of oral ulcer wounds. It also has good adhesion to other tissues and organs, and can be used in the field of tissue repair to play a good role in reducing tension and promoting tissue healing.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a long-term strong adhesion tissue repair patch, characterized in that: The method comprises the following steps: adding an adhesive component, an anti-swelling component and α-ketoglutaric acid in proportion to a colloidal aqueous solution of a patch matrix material, and mixing them evenly to obtain a precursor solution; The adhesive component comprises an adhesive component A, an adhesive component B and an adhesive component C, wherein the adhesive component A contains a carboxyl group, the adhesive component B contains a hydroxyl group, and the adhesive component C contains a thiol group; The precursor solution is poured into a patch mold, UV-cured, and the obtained gel is dried to obtain a patch.

2. The method for preparing a long-term strong adhesion tissue repair patch according to claim 1, characterized in that: The patch matrix material is selected from one or more of hyaluronic acid, carboxymethyl cellulose, carrageenan, agar, poly(N-isopropylacrylamide), polyvinyl pyrrolidone, poly(hydroxyethyl methacrylate), poly(glycerol methacrylate), gelatin or polyvinyl alcohol; Preferably, the patch matrix material is gelatin.

3. The method for preparing the long-term strong adhesion tissue repair patch according to claim 1, characterized in that: The adhesion component A is selected from at least one of acrylic acid, NHS-acrylic acid or methacrylic acid; Preferably, the adhesive component A is acrylic acid or NHS-acrylic acid; Or, the adhesion component B is selected from at least one of tannic acid, caffeic acid, dopamine hydrochloride, gallic acid or pyrogallol; Preferably, the adhesion component B is tannic acid; Or, the adhesion component C includes but is not limited to α-lipoic acid, cysteine, glutathione or taurine; Preferably, the adhesion component C is α-lipoic acid.

4. The method for preparing the long-term strong adhesion tissue repair patch according to claim 3, characterized in that: The anti-swelling component is selected from at least one of 2-phenoxyethyl acrylate, polydimethylsiloxane, n-hexane, hexadecanol or cholesterol; Preferably, the anti-swelling component is 2-phenoxyethyl acrylate.

5. The method for preparing the long-term strong adhesion tissue repair patch according to claim 1, characterized in that: The mass ratio of the patch matrix material, water, adhesive component, anti-swelling component and α-ketoglutaric acid is (0.6-1.2): (1-2): (1-3.5): (0.15-0.3): (0.02); In the adhesion component, the mass ratio of adhesion component A, adhesion component B and adhesion component C is (0.1-1):(0.1-1):(0.1-1).

6. The method for preparing the long-term strong adhesion tissue repair patch according to claim 4, characterized in that: The mass ratio of the patch matrix material, water, acrylic acid, NHS-acrylic acid, α-ketoglutaric acid, 2-phenoxyethyl acrylate, α-lipoic acid and tannic acid is 0.6-1.2: 1-2: 1-3.5: 0.15-0.3: 0.01-0.02: 0.05-0.2: 0.1-1: 0.1-1.

7. The method for preparing a long-term strong adhesion tissue repair patch according to claim 1, characterized in that: The temperature for drying the gel obtained by UV curing is 25-45° C. and the drying time is 12-24 hours.

8. The method for preparing a long-term strong adhesion tissue repair patch according to claim 1, characterized in that: The material of the patch mold is selected from one or more of polytetrafluoroethylene, PDMS, silicone or glass mold; Preferably, the patch mold is a glass mold, and the thickness of the glass mold is 0.1-2 mm.

9. The method for preparing a long-term strong adhesion tissue repair patch according to claim 1, characterized in that: The power of UV curing lamps is 10w-500w, and the UV curing time is 2min-12h; Preferably, the UV lamp power is 500W for curing for 2-10 minutes.

10. A long-term strong adhesion tissue repair patch, characterized in that: The patch is prepared by the preparation method of the long-term strong adhesion tissue repair patch according to any one of claims 1-9.

Citation Information

Cited By

  • Environment-friendly biomass-based underwater adhesive as well as preparation method and application thereof

    CN121518096A

  • Oral ulcer pasting film and preparation method thereof

    CN121622623A